Acute appendicitis in pregnancy, is there a role for conservative management? - Tian, Jane; Altai, Tabark; Bhatia, Shubham; Mourad, Youssef; Miele, Andrew; Robitsek, R. Jonathan; Mckenzie, Katherine; Louis, Martine A.; Mandava, Nageswara R. (International Surgery Journal, 2024)
Background: Although rare, acute appendicitis is the most common general surgery problem encountered in pregnancy. A chief concern is timely and accurate diagnosis. Traditionally, delayed diagnosis of appendicitis in pregnant patients can quickly lead to appendiceal rupture associated with miscarriage, premature delivery, or even fetal loss. Hence, appendectomy has been the gold standard. However, emerging evidence suggests conservative management may be more effective than previously thought, after accounting for maternal and fetal characteristics. Methods: This retrospective study included a sample of pregnant women diagnosed with acute appendicitis presenting for treatment to two hospitals in Queens, NY, between Jan 2012 and Dec 2021. The characteristics, presentation, and outcomes of conservatively versus surgically treated patients were compared. Results: The cumulative incidence of acute appendicitis was 0.11% (n=44/28,000). Forty were treated surgically: 78% underwent laparoscopic appendectomy, 15% open appendectomy, and 8% underwent an initial laparoscopy which was converted to an open appendectomy. Four (14%) patients were managed conservatively with IV antibiotics. Eight percent of patients treated surgically had postoperative complications. Neither surgical nor conservatively treated groups reported any instance of mortality or fetal demise. Conclusions: Our study adds to the literature on treatment decisions for pregnant patients with acute appendicitis. Although surgical intervention remains the gold standard, it carries the potential risk of peri- and postoperative complications. These findings suggest conservative management with antibiotics can sometimes be used without a negative impact on maternal or fetal outcomes.